Evaluation of the injection moulding conditions in soy/nanoclay based composites. (October 2017) - Bourny, V.; Perez-Puyana, V.; Felix, M.; Romero, A.; Guerrero, A.
Graphical abstract: Highlights: Protein/nanoclay mixing determines the integration of the nanoclay particles. An increase of injection pressure induces an increase in tensile properties. Changes in mixing time have a remarkable effect on water uptake capacity. Mechanical and techno-functional properties of composites has been improved. Nanocomposites obtained would be suitable for certain commercial applications. Abstract: Biocomposites, and generally bio-based plastics, are seen as a promising alternative to conventional plastics because they are based on renewable natural components (eco-friendly) with a lower cost. Biocomposites using soy protein and glycerol were obtained with an injection moulding technique as the thermoprocessing method. Nanoclay (Montmorillonite, MMT-Na + ) was included to improve physicochemical properties of novel SPI/MMT nanocomposites prepared by injection moulding, primary attending to water uptake capacity (WUC), but also considering rheological and mechanical properties. The influence of processing conditions has been studied in order to assess the modifications taking place in the microstructure and properties of these nanocomposites. Addition of MMT-Na + improves mechanical properties and WUC of SPI-based materials, depending on processing conditions. Injection pressure only exerts a slight enhancement of mechanical properties and WUC. However, an increase in mixing time leads to a relevant increase in WUC without impairing the mechanical properties of nanocomposites.